Physico-chemical modification of gelatine for the improvement of 3D printability of oxidized alginate-gelatine hydrogels towards cartilage tissue engineering. (October 2021) - Kreller, T.; Distler, T.; Heid, S.; Gerth, S.; Detsch, R.; Boccaccini, A.R.
Graphical abstract: Highlights: Bioprinting of alginate dialdehyde-gelatine demonstrated for cartilage tissue engineering. Thermal pre-treatment of gelatine affects hydrogel mechanical and rheological characteristics. Thermal pre-treatment of gelatine enables 3D printing of hierarchical complex structures. Abstract: This work explored 3D printing to mimic the intrinsic hierarchical structure of natural articular cartilage. Alginate di-aldehyde- gelatine (ADA-GEL) hydrogel was used as ink to create hierarchically ordered scaffolds. In comparison to previously reported ADA-GEL compositions, we introduce a modified formulation featuring increased amounts of thermally modified gelatine. Gelatine was degraded by hydrolysis which resulted in tailorable printability characteristics further substantiated by rheological analysis. ADA (3.75 %w/v)-GEL (7.5 %w/v) with gelatine modified at 80 °C for 3 h could be printed in hierarchical complex structures reaching scaffold heights of over 1 cm. The hierarchical structure of the scaffolds was confirmed via µCT analysis. To examine mechanical properties as well as the suitability of the hydrogel as a proper matrix for cell seeding and encapsulation, nanoindentation was performed. Elastic moduli in the range of 5 kPa were measured. Gelatine heat pre-treatment resulted in modifiable mechanical and rheological characteristics of ADA-GEL. In summary, this study demonstrates the possibility to enhance the printability of ADA-GEL hydrogels to fabricate hierarchical scaffold structures with shape stability and fidelity, without the necessity to change the initial hydrogel chemistry by the use of additives or crosslinkers, providing a valuable approach for fabrication of designed scaffolds for cartilage tissue engineering.